2020
DOI: 10.1021/acs.jpca.0c00803
|View full text |Cite
|
Sign up to set email alerts
|

Site-Selective Orbital Interactions in an Ultrathin Iron-Carbene Photosensitizer Film

Abstract: We present the first experimental study of the frontier orbitals in an ultrathin film of the novel hexa-carbene photosensitizer [Fe(btz) 3 ] 3+ , where btz is 3,3′dimethyl-1,1′-bis(p-tolyl)-4,4′-bis(1,2,3-triazol-5-ylidene). Resonant photoelectron spectroscopy (RPES) was used to probe the electronic structure of films where the molecular and oxidative integrities had been confirmed with optical and X-ray spectroscopies. In combination with density functional theory calculations, RPES measurements provided dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 30 publications
4
16
0
Order By: Relevance
“…These non-trivial metal-ligand bonding properties were further detailed in a recent study combining optical characterization with resonant photoemission X-ray spectroscopy of thin films of complex 25(III). [96] This study firstly confirmed the integrity of the Fe(III) oxidation state for thin films, thus broadening the potential range of viable applications towards thin film technologies significantly. Secondly, the presented X-ray spectroscopic results elucidated the involvement of the different ligand constituents to different molecular orbital components of the valence electronic structure in significant detail.…”
Section: Photoluminescent Fe(iii) Hexa-carbene Complexessupporting
confidence: 56%
“…These non-trivial metal-ligand bonding properties were further detailed in a recent study combining optical characterization with resonant photoemission X-ray spectroscopy of thin films of complex 25(III). [96] This study firstly confirmed the integrity of the Fe(III) oxidation state for thin films, thus broadening the potential range of viable applications towards thin film technologies significantly. Secondly, the presented X-ray spectroscopic results elucidated the involvement of the different ligand constituents to different molecular orbital components of the valence electronic structure in significant detail.…”
Section: Photoluminescent Fe(iii) Hexa-carbene Complexessupporting
confidence: 56%
“…4 as a basis for the subsequent discussions of the RPES data. Unlike , which we have previously discussed in detail 35 , is a closed-shell complex. The LUMO (lowest unoccupied MO) is almost entirely of character and located on the bpy ligand (MO-235).…”
Section: Resultsmentioning
confidence: 88%
“…XAS and emerging time-resolved X-ray techniques 27 have contributed to a better understanding of the properties of iron–carbene photosensitisers in terms of electronic structure 28 31 , excited-state deactivation pathways 32 , and excited-state dynamics such as hot branching 33 and wave packet oscillations 34 . We have also used resonant photoelectron spectroscopy (RPES) to probe site-selective orbital interactions in 35 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations